(untitled) (Malaysian Journal of Learning and Instruction, 2013)
Purpose – The present study investigated whether or not the benefits of interleaving of exemplars from several categories vary with retention interval in inductive learning. Methodology – Two experiments were conducted using paintings (Experiment 1) and textual materials (Experiment 2), and the experiments used a mixed factorial design. Forty students participated in each experiment for course credit. In each experiment, participants studied a series of exemplars from several categories which were presented massed and interleaved, and later their induction was tested either shortly after the study phase (short-term retention) or after a week’s delay (long- term retention). Findings – Consistent with findings from previous studies, the interleaving effect was found in the short-term retention condition, and crucially, the present study provided the initial evidence that interleaving of exemplars also affected long-term retention. Interestingly, massing was judged to be more effective than spacing (interleaving) in most groups, even when actual performance showed the opposite. Significance – The present study shows that interleaved exemplars have considerable potential in improving inductive learning in the long term. For example, induction is used in case-based reasoning which requires one to start with learning from specifi c cases, and then form generalizations of these cases by identifying the commonalities between them. In order to enhance long-term retention, educators may want to consider using interleaved presentation rather than massed presentation in teaching examples or cases from a particular category or concept.